Multiple Magma Sources Beneath the Okmok Caldera as Inferred From Local Earthquake Tomography. Issue 10 (20th October 2022) - Kasatkina, Ekaterina; Koulakov, Ivan; Grapenthin, Ronni; Izbekov, Pavel; Larsen, Jessica F.; Al Arifi, Nassir; Qaysi, Saleh Ismail
Abstract: Okmok volcano located on the northeastern part of the Umnak Island is one of the most active volcanoes in the Aleutian Arc. It was initially built as a large shield volcano, but 12, 000 and 2, 050 years ago, it experienced two caldera‐forming eruptions that destroyed the central part of the volcano. The post‐caldera eruptions have occurred mostly along the inner perimeter of the caldera from cinder and tuff cones. Here, we use the local earthquake data of the Alaska Volcano Observatory (AVO) in the time period from 2003 to 2017 to build a model with the 3D distributions of the P and S wave velocities and Vp/Vs ratio. At depths of more than 10 km, we observe a vertically aligned anomaly of high Vp/Vs ratio interpreted as a long‐lived conduit likely responsible for the volcano evolution since its origin. Above this conduit, we reveal a large anomaly of high Vp/Vs ratio representing the main magma reservoir that is connected with several shallow anomalies located below the centers of recent eruptions in the caldera. One of such anomalies represents a large shallow reservoir below the Cone A, which was the source of most of Okmok's historical eruptions. The most recent eruption occurred in 2008 and was fed by a magma diapir that was initially formed in the central magma reservoir and then slowly ascended through a ductile silica rich layer at depths from 6 to 2 km. This interpretation is consistent with the petrology studies and modeling of ground deformations. Plain Language Summary: Okmok is one of the most active volcanoes of the Aleutian Arc. Initially it was formed as an isometrical shield volcano, which was later destroyed by two caldera‐forming eruptions. The post‐caldera activity mostly occurred at several cones distributed along the inner perimeter of the caldera. The latest eruption with the explosivity index of VEI 4 took place in 2008. This eruption, which produced a new large cone Ahmanilix in the northeastern part of the caldera, was significantly different in composition and eruption style compared to other intra‐caldera eruptions. We present a new seismic tomography model, which was constructed based on the arrival times of the P and S waves from local seismicity. Below 10 km depth, we observe an anomaly of high Vp/Vs ratio, which may represent a steady magma conduit that is responsible for the long‐term formation of the entire Okmok volcanic complex. In the upper crust, the model reveals a series of separate local magma sources beneath volcanic centers where historical eruptions took place. The 2008 eruption was fed by a magma diapir that was initially formed in the deep conduit and then slowly ascended through a ductile layer at depths from 6 to 2 km. Key Points: The new crustal model beneath the Okmok Caldera with the 3D distributions of Vp, Vs and Vp/Vs ratio reveals the geometry of magma sources Below 10 km depth, an anomaly of high Vp/Vs ratio indicates the location of the main magma conduit that fed the long‐term formation of Okmok At shallow depths, seismic anomalies reveal several magma sources that fed eruptions along the inner perimeter of the caldera